2022
DOI: 10.1002/btm2.10459
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular nanoparticles to attenuate both reactive oxygen species and inflammatory damage for treating Alzheimer's disease

Abstract: Prevention and early intervention are the current focus of treatment for Alzheimer's disease (AD). An increase in reactive oxygen species (ROS) is a feature of the early stages of AD, thus suggesting that the removal of excess ROS can be a viable method of improving AD. Natural polyphenols are able to scavenge ROS and thus promising for treating AD. However, some issues need to be addressed. Among them, important are that most polyphenols are hydrophobic, have low bioavailability in the body, are easily degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
2
0
0
Order By: Relevance
“…Zhang et al 61] showed that AD patients have significantly elevated levels of ROS in the brain, experiencing OS. The high intracellular ROS levels in the H 2 O 2 group found in our study are similar to those reported by Zhang et al [77] in patients with AD. However, while the study of Zhang et al [77] included patients with AD, our study included PC-12 cells induced by OS with H 2 O 2 (in vitro ND model).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Zhang et al 61] showed that AD patients have significantly elevated levels of ROS in the brain, experiencing OS. The high intracellular ROS levels in the H 2 O 2 group found in our study are similar to those reported by Zhang et al [77] in patients with AD. However, while the study of Zhang et al [77] included patients with AD, our study included PC-12 cells induced by OS with H 2 O 2 (in vitro ND model).…”
Section: Discussionsupporting
confidence: 92%
“…The high intracellular ROS levels in the H 2 O 2 group found in our study are similar to those reported by Zhang et al [77] in patients with AD. However, while the study of Zhang et al [77] included patients with AD, our study included PC-12 cells induced by OS with H 2 O 2 (in vitro ND model). In research conducted by Zhang et al [78], the EPS from L. plantarum YW11 displayed a remarkable scavenging ability, with IC 50 values against hydroxyl radical of 75.10% and 1.22 mg/mL, and against superoxide anion radical of 62.71% and 1.54 mg/mL.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, the clinical utility of these pharmacological agents is hampered by challenges such as limited absorption, chemical instability, and suboptimal efficacy, which impose constraints on their widespread momentum in the medicament of free radical-associated diseases [156]. Certain studies have demonstrated that conjugated or functionalized NPs can cross the blood-brain barrier (BBB) and exhibit their neuroprotective role against ROS-mediated neuronal toxicity and brain inflammation [160][161][162][163].…”
Section: Role Of Nanoparticles (Nps) As Reactive Oxygen Species (Ros)...mentioning
confidence: 99%